2019
DOI: 10.1016/j.jsams.2019.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute aerobic and resistance exercise on executive function: An ERP study

Abstract: Objectives: This study addressed the effects of acute, moderate-intensity aerobic and resistance exercise on the shifting aspect of cognition following a 30-min recovery period. It also explored the neuro-electrical activation that underlies the relationship between acute exercise and cognitive function through the examination of P3b and N1 components of event-related potentials. Design: A counterbalanced, repeated-measures experimental design. Methods: Thirty-five volunteer young adults completed two experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 31 publications
2
31
0
1
Order By: Relevance
“…The present findings suggest that faster cognitive processing to detect and process a stimulus in the environment [ 73 ] and more attentional resources allocated to process late general inhibition can be induced following acute exercise in obese individuals. Similarly, improvements in inhibition as assessed by the ERP P3 component of the cognitive tasks (e.g., task-switching, visuospatial attention task, and the Flanker task) following acute aerobic and resistance exercise interventions have also been reported in young [ 14 , 23 , 48 ] and older adults [ 10 ] as well as in individuals with developmental coordination disorders [ 9 ] and mild cognitive impairment [ 25 ], suggesting that acute exercise has a greater influence on cognitive functions involving diverse inhibitory control demands.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The present findings suggest that faster cognitive processing to detect and process a stimulus in the environment [ 73 ] and more attentional resources allocated to process late general inhibition can be induced following acute exercise in obese individuals. Similarly, improvements in inhibition as assessed by the ERP P3 component of the cognitive tasks (e.g., task-switching, visuospatial attention task, and the Flanker task) following acute aerobic and resistance exercise interventions have also been reported in young [ 14 , 23 , 48 ] and older adults [ 10 ] as well as in individuals with developmental coordination disorders [ 9 ] and mild cognitive impairment [ 25 ], suggesting that acute exercise has a greater influence on cognitive functions involving diverse inhibitory control demands.…”
Section: Discussionmentioning
confidence: 93%
“…In spite of a lack of behavioral improvement in obese women induced by the acute aerobic-and-resistance exercise intervention when performing the Stroop task in the present study, beneficial effects on cognitive electrophysiological signals as measured by brain ERPs were observed in this study. Indeed, increased Stroop interference-related activation in the dorsolateral prefrontal cortices due to an acute bout of a combination of aerobic and resistance exercise was reported in healthy young adults [ 48 ]. Although the ERP P2 component is extremely sensitive to arousal levels [ 60 , 61 ], P2 latency and amplitude were not significantly improved after an exercise intervention in the EG in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, it has been demonstrated that an acute PE brings benefits for some ways of performance on cognitive tasks after exercise. By the same token, executive functions improve after PE (Wu et al, 2019). Recent studies, however, affirm that there is not enough evidence that PE is positive for cognition or brain function and structure in child and young samples (Gunnell et al, 2018).…”
Section: Introductionmentioning
confidence: 96%